2020
DOI: 10.5483/bmbrep.2020.53.5.041
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine attenuates tamoxifen-induced toxicity in human retinal pigment epithelial cells

Abstract: Tamoxifen, a nonsteroidal estrogen receptor (ER) antagonist, is used routinely as a chemotherapeutic agent for ER-positive breast cancer. However, it is also causes side effects, including retinotoxicity. The retinal pigment epithelium (RPE) has been recognized as the primary target of tamoxifen-induced retinotoxicity. The RPE plays an essential physiological role in the normal functioning of the retina. Nonetheless, potential therapeutic agents to prevent tamoxifen-induced retinotoxicity in breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…TLR4 was directly related with NLRP3 and PYCARD demonstrated a positive synergistic correlation supporting malignant phenotypes, although the correlation factor was not strong. Reciprocal crosstalk between the NLRP3 inflammasome and TLR4 is not a surprise in other malignancies ( 40 , 41 ) but for the first time, we found a direct indication of their interaction in our BC patients.…”
Section: Discussionsupporting
confidence: 67%
“…TLR4 was directly related with NLRP3 and PYCARD demonstrated a positive synergistic correlation supporting malignant phenotypes, although the correlation factor was not strong. Reciprocal crosstalk between the NLRP3 inflammasome and TLR4 is not a surprise in other malignancies ( 40 , 41 ) but for the first time, we found a direct indication of their interaction in our BC patients.…”
Section: Discussionsupporting
confidence: 67%
“…In the development of cancer, the expression level of GSDMs in cancer cells is usually lower than that in normal tissues due to the high methylation of the promoters of pyroptosis-related genes, resulting in the growth and metastasis of tumors ( Kim et al, 2008 ; Croes et al, 2017 ). Chemotherapy drugs and tamoxifen can inhibit the progression of tumors by inducing pyroptosis of tumor cells ( Hu et al, 2020 ; Hwang and Chung, 2020 ). It has been proven that the expression level of GSDMs was closely related to the prognosis of BC ( de Beeck et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It locally secretes complement components as C1q, complement factor B (CFB), complement component 4 (C4), CFI, and CFH [ 20 , 21 , 22 , 23 ]. We and others showed that complement secretion is modified by external stress [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Additionally, generation of complement activation products, such as anaphylatoxins and opsonins, by healthy and stressed RPE cells independent of any external complement source is described [ 21 , 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%